Misurare le leggi del tempo: considerazioni preliminari su "Vremja – mera mira" di V. Chlebnikov - Luca Cortesi; Alessandro Alberto Trani (eSamizdat)
In this paper we aim to analyse those elements, which can formally ascribed to Math, in the essay "Vremja – mera mira", written by Velimir Khlebnikov between 1915-1916. This text has been largely neglected to date, most likely due to the complex mathematical language employed by Khlebnikov. We propose a reconstruction and an interpretation of most of the mathematical expressions used by Khlebnikov, including a passage that explains the origin of the number 48 - a number ubiquitous in Khlebnikov's "scientific" works. We also highlight some evidence suggesting that Khlebnikov's ideas were influenced by the ideas of Sir Rowan Hamilton. In particular, we argue that Khlebnikov re-elaborated Hamilton's interpretation of Algebra as the Science of Pure Time: in Khlebnikov's view, Algebra does not only derive from the notion of Time but can reveal the nature of Time itself.